Motor imagery practice and skilled performance in sport: From efficacy to mechanisms - Moran, A.; O`Shea, H. (Skill acquisition in sport: research, theory and practice, 2020)
In this chapter we reviewed the nature and characteristics of motor imagery and the eflicacy of, and neurocognitive mechanisms underlying motor imagery practice in sport. We began by defining motor imagery, indicating that it shares certain mental representations and neural circuits with executed action. Then, we defined motor imagery practice and illustrated its use among athletes and explained how it has been studied experimentally in psychology. We also summarized the main research findings on the eflicacy of motor imagery practice in enhancing skilled performance in sport. We reviewed motor simulation theory to help explain what is known about the neurocognitive mechanisms underlying motor imagery. Finally, we outlined some new directions for future research on motor imagery in sport.